Multidisciplinary Energy Assessment of Tertiary Buildings: Automated Geomatic Inspection, Building Information Modeling Reconstruction and Building Performance Simulation - Faustino Patiño-Cambeiro; Guillermo Bastos; Julia Armesto; Faustino Patiño-Barbeito (Energies, 2018)
The authors would like to add the student Luis Gandarela Campos, from the University of Vigo, that contributed in some technical computations, in the Acknowledgement Section of their paper published in Energies [1].[...]